A facile approach for development of a vaccine made of bacterial double-layered membrane vesicles (DMVs). (December 2018) - Wang, Sihan; Gao, Jin; Li, Mo; Wang, Liguo; Wang, Zhenjia
Abstract: Bacterial infections cause acute and chronic diseases. Antimicrobial resistance and aging-related immune weakness remain challenging in therapy of infectious diseases. Vaccines are however an alternative to prevent bacterial infections. Here we report a facile method to rapidly generate bacterium-membrane-formed nanovesicles as a vaccine using nitrogen cavitation. The vaccine is comprised of double-layered membrane vesicles (DMVs) characterized by cryo-TEM, biochemistry and proteomics, showing DMVs possess the integrity of bacterial membrane and contain a wide range of membrane proteins required for vaccination. In the mouse sepsis model induced by Pseudomonas aeruginosa, we found that DMVs can improve mouse survival after mice were immunized with DMVs. The increased adaptive immunity and unique biodistribution of DMVs were responsible for enhanced protection of bacterial infection. Our studies demonstrate that this simple and innovative approach using nitrogen cavitation would be a promising technology for vaccine developments.